Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the length of the third side of a triangle when we know the lengths of two sides and the angle between them, we can use the Law of Cosines. The Law of Cosines formula is given by:
[tex]\[ c^2 = a^2 + b^2 - 2ab \cos(\theta) \][/tex]
where:
- [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are the lengths of the two known sides,
- [tex]\( \theta \)[/tex] is the included angle,
- [tex]\( c \)[/tex] is the length of the third side.
In this problem, we know:
- [tex]\( a = 2 \)[/tex]
- [tex]\( b = 3 \)[/tex]
- [tex]\( \theta = 60^\circ \)[/tex]
First, we need to convert the angle from degrees to radians, since the cosine function in the Law of Cosines formula often requires the angle in radians.
[tex]\[ \theta = 60^\circ = \frac{\pi}{3} \][/tex]
Next, we apply the Law of Cosines formula:
[tex]\[ c^2 = 2^2 + 3^2 - 2 \cdot 2 \cdot 3 \cdot \cos\left(\frac{\pi}{3}\right) \][/tex]
We know that:
[tex]\[ \cos\left(\frac{\pi}{3}\right) = 0.5 \][/tex]
Therefore, substituting these values into the formula gives:
[tex]\[ c^2 = 4 + 9 - 2 \cdot 2 \cdot 3 \cdot 0.5 \][/tex]
[tex]\[ c^2 = 4 + 9 - 6 \][/tex]
[tex]\[ c^2 = 7 \][/tex]
To find [tex]\( c \)[/tex], we take the square root of both sides:
[tex]\[ c = \sqrt{7} \][/tex]
Thus, the length of the third side of the triangle is:
[tex]\[ \boxed{\sqrt{7}} \][/tex]
[tex]\[ c^2 = a^2 + b^2 - 2ab \cos(\theta) \][/tex]
where:
- [tex]\( a \)[/tex] and [tex]\( b \)[/tex] are the lengths of the two known sides,
- [tex]\( \theta \)[/tex] is the included angle,
- [tex]\( c \)[/tex] is the length of the third side.
In this problem, we know:
- [tex]\( a = 2 \)[/tex]
- [tex]\( b = 3 \)[/tex]
- [tex]\( \theta = 60^\circ \)[/tex]
First, we need to convert the angle from degrees to radians, since the cosine function in the Law of Cosines formula often requires the angle in radians.
[tex]\[ \theta = 60^\circ = \frac{\pi}{3} \][/tex]
Next, we apply the Law of Cosines formula:
[tex]\[ c^2 = 2^2 + 3^2 - 2 \cdot 2 \cdot 3 \cdot \cos\left(\frac{\pi}{3}\right) \][/tex]
We know that:
[tex]\[ \cos\left(\frac{\pi}{3}\right) = 0.5 \][/tex]
Therefore, substituting these values into the formula gives:
[tex]\[ c^2 = 4 + 9 - 2 \cdot 2 \cdot 3 \cdot 0.5 \][/tex]
[tex]\[ c^2 = 4 + 9 - 6 \][/tex]
[tex]\[ c^2 = 7 \][/tex]
To find [tex]\( c \)[/tex], we take the square root of both sides:
[tex]\[ c = \sqrt{7} \][/tex]
Thus, the length of the third side of the triangle is:
[tex]\[ \boxed{\sqrt{7}} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.